Methods for Increasing Accuracy in the Process of Information Exchange and Processing - A. M. Mehdiyeva; I. Z. Sardarova; S. V. Quliyeva (Novel Research Aspects in Mathematical and Computer Science Vol. 4, 2022)
In the research work discusses the problem of eliminating errors that arise at the processing stage, taking into account the growing need for digital signal processing of measurement results in the oil and gas industry. At the research work addresses the problem of eliminating errors that occur during the processing stage, taking into account the increased demand for digital signal processing of measurement results in the oil and gas industry. We investigated the problems associated with corrective filtering and discrete averaging in digital signal processing. The proposed approach to the creation of information-measuring systems of the parameters under consideration consists of a cumulative analysis of measurement processes and corrective filtration with the aim of achieving balanced metrological, structural, algorithmic and functional indicators of the effectiveness of the developed tools. Thus, the proposed approach to improve the accuracy of measurement objectives is a comprehensive analysis of measurement processes and a corrective filter to provide a balanced assessment of the effectiveness, structural and functional efficiency of the developed algorithmic tools. In the research work discusses the problem of eliminating errors that arise at the processing stage, taking into account the growing need for digital signal processing of measurement results in the oil and gas industry. And investigated the problems with equalizing filtering and discrete averaging in digital signal processing. Therefore, it can be said that the numerical mean operator applied for both types of error correction is intended for any error. This has been proven by modeling in program Matlab. A mathematical model is proposed for evaluating the noise immunity characteristics of a coherent modem reception in a message transmission system that functions under the influence of unintended interference sources. The developed mathematical model takes into account the demodulator synthesis algorithm, decoding methods, effective M-PSK modulations and Reed-Solomon codes in the modem. Integrated expressions are obtained that evaluate the noise immunity characteristics of a modem receive, taking into account the energy performance of the receiver.